Job search, locus of control, and internal migration - Marco Caliendo; Deborah A. Cobb-Clark; Juliane Hennecke; Arne Uhlendorff (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Internal migration can substantially improve labor market efficiency. Consequently, policy is often targeted towards reducing the barriers workers face in moving to new labor markets. In this paper we explicitly model internal migration as the result of a job search process and demonstrate that assumptions about the timing of job search have fundamental implications for the pattern of internal migration that results. Unlike standard search models, we assume that job seekers do not know the true job offer arrival rate, but instead form subjective beliefs - related to their locus of control - about the impact of their search effort on the probability of receiving a job offer. Those with an internal locus of control are predicted to search more intensively (i.e. across larger geographic areas) because they expect higher returns to their search effort. However, they are predicted to migrate more frequently only if job search occurs before migration. We then test the empiricalimplications of this model. We find that individuals with an internal locus of control not only express a greater willingness to move, but also undertake internal migration more frequently.
Keywords: J61; 330; Locus of Control; Internal Migration; Mobility; Job Search